Integrasi Pembelajaran Pendidikan Agama Islam Dalam Pembelajaran Matematika Sebagai Upaya Penguatan Pendidikan Karakter Siswa - Rusydiyah, Evi Fatimatur; Rahman, Moh. Rifqi; Wulandari, Luluk; Abidin, Achmad Zainal (TADRIS: Jurnal Pendidikan Islam, 2023)
Character education in Indonesia can be done through “meaning learning”. It is by integrating the learning of Islamic Religious Education and Mathematics. This integration will expand Mathematics so that it is not only a learning with symbols, but also a meaningful learning. The research method used quantitative experimental to determine the effect of treatment integration of Islamic religious education learning with mathematics. Thus, this study divides the object of research into two groups, namely experimental and control. Data analysis in this study used independent sample t-test. The results showed that there was a significant difference between the mean of the experimental and control groups, the experimental mean had a higher mean value. While the results of the independent sample t-test test showed a significance value of 0,009 < 0,05 so that H0 was rejected and H1 was accepted. The integration of Islamic religious education learning in mathematics has proven to be influential as an effort to strengthen student character education. Thus this study shows a successful learning integration model in improving learning outcomes in the form of character education.